2011
DOI: 10.1089/mdr.2010.0170
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Patients with Pseudomonas aeruginosa Bacteremia: Clinical Impact of Antimicrobial Resistance on Outcome

Abstract: Despite the high prevalence of antimicrobial resistance among Pseudomonas aeruginosa bacteremia, the clinical consequence of resistance remains unclear. The purpose of this study was to identify predictors of mortality and evaluate the clinical impact of antimicrobial resistance on outcome in P. aeruginosa bacteremia. A retrospective cohort study including patients with P. aeruginosa bacteremia was performed. The risk factors for antimicrobial resistances were evaluated, and the impact of the respective resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
72
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 28 publications
7
72
2
Order By: Relevance
“…This rate was reported as 51.1% in the study of Pinheiro et al (27) and 25.2% in the study of Joo et al (31). The reason for lower mortality in our study than in other studies is that those studies were conducted among intensive care patients or patients with bacteremia.…”
Section: şImşek Et Al Susceptibility Patterns Of Pseudomonas Aeruginosacontrasting
confidence: 39%
“…This rate was reported as 51.1% in the study of Pinheiro et al (27) and 25.2% in the study of Joo et al (31). The reason for lower mortality in our study than in other studies is that those studies were conducted among intensive care patients or patients with bacteremia.…”
Section: şImşek Et Al Susceptibility Patterns Of Pseudomonas Aeruginosacontrasting
confidence: 39%
“…The occurrence of primary P. aeruginosa BSI infections in the hematology population is well described [12][13][14]. High rates of corticosteroid use were also described in the P. aeruginosa primary BSI cohort described by Joo et al [15]. Thus these two variables place an individual at risk for not only a primary BSI but also for its recurrence.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors have identified resistance to ceftazidime, carbapenems, or MDR as risk factors for mortality (1,7,16,24,25,28). In contrast, Combes et al (3) evaluated the impact of piperacillin resistance on the outcomes of P. aeruginosa ventilator-associated pneumonia in patients who received appropriate empirical antibiotics, and they found that piperacillin resistance was not associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of multidrug resistance on the probability of receiving appropriate empirical therapy was not evaluated. Some authors have described a higher mortality rate among patients with MDR strains (1,7,8,10,16,25,28), but these patients more frequently received incorrect empirical therapy and had more severe underlying diseases and longer hospital stays than patients infected by susceptible Pseudomonas aeruginosa strains (24). Therefore, the individual influence of each one of these variables on the mortality of PAB is still not well defined.…”
mentioning
confidence: 99%